Local roots, global vines: Human rights museums in western Japan as expressions of identity. (15th February 2023) - Mueller, Lisa
Abstract: Recently human rights movements among Japan's Buraku people have become increasingly globalized, situating the Buraku struggle among those of other caste‐based minorities around the world. Scholars have theorized that this globalization manifests in a global–local feedback loop in which decisions made by global and local actors inform one another. In this study, I utilize field research and qualitative content analysis of brochures at three Buraku human rights museums in western Japan to investigate this global reorientation. I show that two museums correspond to global–local feedback loop theory and I further identify how local nuances affect the disparate strategies the museums employ to engage with this new globalized Buraku identity. The third museum, however, serves as a counterexample by electing to keep its exhibits locally focused, reflecting its community‐driven mission. I argue that these museums function as interlocutors of Buraku identity at both the local and global levels.